Effect of vitamin C and vitamin E supplementation on lipid peroxide of lactating woman - Endang Sri Sunarsih, Prasetyastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Vitamin C and vitamin E are antioxidants that trapp free radical that is continuously formed in aerobic organism as an effect of aerobic respiration in mitochondria and substrate oxidation. The quantity and quality of breast feeding (ASH are influenced by nutritional status and health of the mother. The ASI vitamin C level is very much related to everyday intake and plasma vitamin C of the mother.Objective: To know the effect of vitamin C and vitamin E supplementation on peroxide lipid (MDA) of lactating women.Methods: This was pretest and post test experimental design. The subjects were twenty three lactating women who live in Pakem District, Sleman 19-38 year olds they received 75 mg vitamin C and 2 mg vitamin E every two days for a period of one month. Blood sample was taken from cubit vein before and after supplementation. Determination of vitamin E level used spectrofluorometer, whereas vitamin C and MDA level were determined by spectrophotometer. The data was analyzed with Pearson correlation test Results: the correlation of vitamin C vs MDA; vitamin E vs MDA and vitamin C together with vitamin E vs MDA were r - 0.528; r square 0.276 and p = 0.05; r -0.671, r square 0.451, p = 0.009 and r 0.690; r square 0.476 and p= 0.028, respectivelyConclusion: the effect of vitamin E to MDA was stronger than vitamin CKeyword.: vitamin C - vitamin E - peroxide lipid - free radical - lactating mother